Heavy metals (copper, zinc and lead) in mangrove sediment at Selangor River, Kampung Kuantan - Zainal, Ahmad Nur Syahmi (2019)
Mangroves are woody plants that grow at the interface between land and sea in tropical and subtropical latitudes where they exist in conditions of high salinity, extreme tides, strong winds, high temperature, and muddy anaerobic soils. The objectives of this study were to determine the selected heavy metals (Cu, Zn, and Pb) contamination in mangrove sediment at Selangor River, Kampung Kuantan, Kuala Selangor and compare heavy metals (Cu, Zn, and Pb) content in mangrove sediment between different plots and different depths. Physical properties (soil moisture and soil texture) and chemical properties (pH water, soil electrical conductivity, heavy metal (Cu, Zn, and Pb) of soil were defined by plots and depths. Data obtained were analyzed using the Statistical Analysis System (SAS) version 9.4 software. The results showed that the sediment was in class sandy clay and soil moisture in all plots and at all depths were higher. Mangrove area in Selangor River contained wet sediment. Contamination of soil by heavy metals affected by many factors, including soil pH and soil electrical conductivity. Element Lead (Pb) was analyzed using Inductively Coupled Plasma (ICP). Element Copper (Cu) and Zinc (Zn) were analysed using Atomic Absorption Spectrometer (AAS). The contamination of sediment with Zn was higher in all plots and at all depths than Cu and Pb. The heavy metal of Copper (Cu), Zinc (Zn) and Lead (Pb) were found in all plots and at all depths. The sediment in all plots and at all depths were contaminated with these heavy metals because of the residential area, industrial, recreational activities, agriculture and fishing in Selangor River.